Prevalence ofOPGand IL-1 gene polymorphisms in chronic periodontitis - Judith Wagner (Blackwell Synergy, 2007)
Aim: To investigate the association of polymorphisms in the osteoprotegerin (OPG) and interleukin 1 (IL-1) genes with chronic periodontitis (CP). Material and Methods: One hundred and ninety-four individuals (97 CP patients, 97 controls) were genotyped for the OPG polymorphisms Lys3Asn and Met256Val and for the IL-1 polymorphisms IL-1A ( 889C/T) and IL-1B (13953C/T). Results: The homozygous variants coding for Lys3 were present at a higher frequency, whereas Asn3 and Met256 were present at a lower frequency in CP patients/controls (Lys3: 31%/25%, Asn3: 23%/32% and Met256: 66%/73%). Heterozygosity for Lys3Asn was observed at a higher frequency in CP patients/ controls (46%/43%). Homozygosity for the Val256 genotype was observed in two CP patients (one in controls). Met256Val heterozygosity was more prevalent in CP patients/controls (32%/20%). All differences were statistically not significant between CP patients and controls. In contrast, both IL-1 polymorphisms were statistically significant. The heterozygous variant for IL-1A was present in 32% of the CP patients and in 20% of the controls (homozygosity (patients/controls) CC: 10%/21% and TT: 55%/33%). Heterozygosity for IL-1B was observed in 37% of the CP patients versus 34% in the controls (homozygosity (patients/controls) CC: 26%/57% and TT: 37%/9%). Conclusion: While the association between the IL-1 polymorphisms and CP was confirmed, no association between the OPG polymorphisms and CP could be found.